NON-EQUIVALENCE GRAMMATICAL VARIATION IN CHILDREN BILINGUAL STORYBOOKS TRANSLATION - Chusna Apriyanti; Dwi Rahayu (LPPM Press STKIP PGRI Pacitan, 2016)
The objectives of this study were to find out the non-equivalence grammatical variation and the probable effects of the occurence of non equivalence between the English version and Bahasa Indonesia in children storybook. The descriptive quantitative research was implemented in this study. There were twenty books as the data source. The researcher collected the data by reading the original and translation children bilingual storybooks, underlining grammatical non-equivalent expression, and classifying those non-equivalences into table. After being collected, the data were analyzed by these procedures: selecting the expression in text 1 and text 2, analyzing the data by using the theory of equivalence, drawing the conclusion. The result showed that there were five types of grammatical non-equivalence. They are person (5.33%), tense (32.52%), voice (4.73%), number (45.56%), and gender (11.83%).